Corruption and economic growth, with a focus on Vietnam - Nguyen-ngoc-Anh (Crime, law and social change, 2016)
Numerous studies have looked at the effect of corruption on economic growth and a common finding is that the former adversely affects the latter. Through regression analyses, we use recent data from Transparency International’s Corruption Perception Index (CPI) and the World Bank’s Governance Indicators for the 2000-2012 period to test the direct and indirect effects of corruption on GDP growth rate. Our findings confirm that corruption metes out important costs in terms of lower economic growth when the direct method is considered. However, the indirect method shows that the impact of corruption on growth through the human capital (education) and domestic investment channels is positive, whereas the impact of corruption on growth through the voice and accountability channel is negative and statistically significant. Using these results, we examine the costs of corruption for Vietnam. We show that, had the CPI levels improved by just one unit between 2000 and 2012, then the economy would have grown from an average of 6.73 % during this period to 6.94 %. If corruption levels had fallen one standard deviation (i.e., the CPI increased from 2.6 to 5.0), then Vietnam could have achieved a growth rate of 7.22 %. This illustrates the primary finding that corruption undermines economic performance.